ANALISIS PEMECAHAN MASALAH OPERASI HITUNG PENJUMLAHAN DAN PENGURANGAN BENTUK ALJABAR SISWA KELAS VIII DITINJAU DARI PERBEDAAN JENIS KELAMIN: Analysis of Problem Solving Algebraic Operations of Addition And Subtraction of Algebraic Forms of Grade VIII Students Reviewed From Gender Differences - Ma'abud, Yusril Y; Lefrida, Rita; Alfisyahra, Alfisyahra; Pathuddin, Pathuddin (Universitas Tadulako, 2024)
This study aims to describe the analysis of problem solving of addition and subtraction operations in the form of aabar. The subjects of the study were 2 people, one male and one female each. Another criterion for the subjects was having high mathematical abilities. Polya's problem solving steps were used in this study. The results of this study are: (1) at the stage of understanding the problem, male and female students with high mathematical abilities can identify things that are known based on declarative sentences and those asked based on question sentences. In addition, the subjects can change verbal sentences into mathematical forms, (2) at the stage of planning the problem, the subjects are able to make connections between known information and the problems asked, (3) at the stage of implementing the problem solving plan, the subjects determine the results of the problems given in the questions by making connections between known information and then for example into algebraic form, after that carry out addition and subtraction operations in algebraic form to get the results of the problems given, (4) at the stage of re-checking, recalculating to be sure of the answer and re-checking each step that has been done.